Risk assessment of lightning protection system using collection volume method at Faculty of Architecture, Planning and Surveyor in UiTM Shah Alam / Haidzum Hazwani Hairi - Hairi, Haidzum Hazwani (2014)
This paper described case study on risk assessment of lightning protection system using Collection Volume Method at Faculty of Architecture, Planning and Surveyor in UiTM Shah Alam. Apparently, lightning is a bright flash of electricity that is produced by a thunderstorm. Malaysia also recorded as second country with the highest number of lightning strikes in the world. Lightning is considered the worst natural killer, causing at least 25,000 deaths worldwide each year [2]. Records stated that the number of lightning in Malaysia was double of that in Florida [2]. But Malaysian is still not aware of its dangers. Risk assessment is a procedure use to detect potential hazard and analyze the possible occurrence happen towards the building and assets by using the suitable lightning protection system (LPS).